2015
DOI: 10.1021/acsmedchemlett.5b00463
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 8-Amino-imidazo[1,5-a]pyrazines as Reversible BTK Inhibitors for the Treatment of Rheumatoid Arthritis

Abstract: Bruton's tyrosine kinase (BTK) is a Tec family kinase with a well-defined role in the B cell receptor (BCR) pathway. It has become an attractive kinase target for selective B cell inhibition and for the treatment of B cell related diseases. We report a series of compounds based on 8-amino-imidazo[1,5-a]pyrazine that are potent reversible BTK inhibitors with excellent kinase selectivity. Selectivity is achieved through specific interactions of the ligand with the kinase hinge and driven by aminopyridine hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Scheme 2 presents the examples of co-crystals of the ligand bearing the 1 backbone in their structures. [3][4][5][6][7][8][9] Although close proximity of O and S atoms is counterintuitive due to the expected lone-pair repulsion between the two atoms, this phenomenon had been noted by Angyán and coworkers in 1987. 10 The intramolecular interaction of carbonyl O atom of proteins with S atom of the ligands was studied by Zhang et al 11 and the strength of the interaction was found to be as strong as a regular H-bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 2 presents the examples of co-crystals of the ligand bearing the 1 backbone in their structures. [3][4][5][6][7][8][9] Although close proximity of O and S atoms is counterintuitive due to the expected lone-pair repulsion between the two atoms, this phenomenon had been noted by Angyán and coworkers in 1987. 10 The intramolecular interaction of carbonyl O atom of proteins with S atom of the ligands was studied by Zhang et al 11 and the strength of the interaction was found to be as strong as a regular H-bond.…”
Section: Introductionmentioning
confidence: 99%
“…In all of the known co‐crystal substructures of 1 with proteins, the 1 moiety adopts a conformer in which the amide O and the thiazole S atoms get close to each other. Scheme 2 presents the examples of co‐crystals of the ligand bearing the 1 backbone in their structures 3–9 …”
Section: Introductionmentioning
confidence: 99%
“…The heterocyclic compounds are essential candidates in the chemical, biological, agricultural, and veterinary elds. 1,2 Among the various heterocycles, imidazo [1,2-a]pyrazine is an aza-heterocyclic compound that has applications as an anticancer agent, 3 cardiac stimulating agent and uterine relaxant, 4 antihyperglycemic agent, 5 antihypertensive agent, 6 antiulcer agent, 7 antibronchospastic agent 8 etc., [9][10][11] The properties of compounds as an application candidate depend upon the molecular structure of the compound and can be tuned by altering the molecular modication, and orientation of the compound. 12 The spatial and chemical constraints in molecular systems give rise to different spatial arrangements or conformations.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a bridgehead nitrogen atom is a common structural motif of these heterocyclic systems. For example, compounds with the imidazo[1,5- a ]pyrazine structure show inhibitory activity against kinases BTK [ 1 ], MEK [ 2 ], ACK1 [ 3 ], mTORC1(2) [ 4 ], c-Src [ 5 ], growth factor IGF-1R [ 6 ] and act as the antagonists of Hedgehog pathway dependent malignancies [ 7 ]. Imidazo[1,5- a ]pyrimidines are inhibitors of the bone morphogenic protein [ 8 ], antitumor agents [ 9 ], and are stimulators of guanylate cyclase [ 10 ], whereas imidazo[1,5- c ]pyrimidines demonstrate anti-infectious effects in the treatment of brucellosis [ 11 ], etc.…”
Section: Introductionmentioning
confidence: 99%